Facial diplegia with paresthesia associated with anti-GD1a antibodies. Issue 3 (4th May 2022) - Strawbridge, Jason; Fu, Katherine A.; Chan, Joy; Flavin, William; Cohen, Joss; Keselman, Inna; Shieh, Perry
Abstract: A 26-year-old previously healthy man presented with progressive facial diplegia and sensory deficits to pinprick in a stocking-glove distribution. Lumbar puncture revealed cytoalbuminologic dissociation, and a nerve conduction study of the right facial nerve demonstrated a proximal demyelinating process. He was started on intravenous immunoglobulin given concern for a Guillain-Barré syndrome variant, and his symptoms improved over several days. This case illustrates the clinical features of facial diplegia with paresthesias, a rare variant of Guillain-Barré syndrome. Unlike most reported cases of facial diplegia with paresthesias that have demonstrated positive anti-ganglioside M2 antibodies, this case is unique given the positivity of anti-ganglioside D1a IgG/IgM antibodies.